Susceptibility to Head Injury during Backward Fall with Side Aligning of the Body - Andrzej Mroczkowski (Applied Sciences, 2020)
(1) Background: The aim of this article is to investigate the susceptibility to head injuries in physical education students who do not train a specific sports discipline and those who use the fall performed backward with side aligning of the body technique. The other goal is the biomechanical analysis of the impact of the fall technique on the likelihood of head injury. (2) Methods: the study included 57 students, divided into two research groups. Group A consisted of 32 students who had not practiced any sport in a sports club before. Group B consisted of 25 students who, by practicing martial arts, had acquired the skill of the fall performed backward with side aligning of the body. A rotating training simulator (RTS) was used to force the fall backwards. (3) Results: students from group B made significantly fewer “head” errors when falling backwards than in group A. Increasing the speed of falling did not increase the number of “head” errors in group B, but only in group A. The type of the fall test performed affected the increase in the number of “head” errors only in group A. (4) Conclusions: practicing selected sports disciplines in which the fall backwards occurs can protect one against head injuries by acquiring appropriate motor habits. The use of the fall performed backward with side aligning of the body technique with the occurrence of horizontal inertia forces causing a fall reduces the risk of head injuries.